1966
DOI: 10.1002/pol.1966.160040607
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic studies of nylon 4. II. On the β and δ polymorphs of nylon 4

Abstract: In addition to the α polymorph, two crystalline forms of nylon 4, the β and δ polymorphs, have been observed and studied. The β polymorph of nylon 4, which has not been found in a pure condition, appears to be similar to the β polymorph of nylon 6. The extended planar zigzag conformation of chains, found in the α polymorph, is present also in the β polymorph. Three models have been proposed to explain the observed data. In model 1, the staggered shear of van der Waals bonded sheets found in the α polymorph is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

1966
1966
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…In similitude with the PA6 patterns deconvolutions and in accordance with the findings in Ref. [28] MP the content of the a-polymorph is very high, the a/b ratio being greater than 11, while the presence of payloads, especially Cu and Fe drastically decreases the ratio to 1e2. Apparently, these metals are strong b-nucleating agents.…”
Section: Crystalline Structure By X-ray Scatteringsupporting
confidence: 89%
See 2 more Smart Citations
“…In similitude with the PA6 patterns deconvolutions and in accordance with the findings in Ref. [28] MP the content of the a-polymorph is very high, the a/b ratio being greater than 11, while the presence of payloads, especially Cu and Fe drastically decreases the ratio to 1e2. Apparently, these metals are strong b-nucleating agents.…”
Section: Crystalline Structure By X-ray Scatteringsupporting
confidence: 89%
“…The a-PA4 with extended planar zig-zag conformation of chains and monoclinic unit cell similar to the a-PA6 was found to predominate in highly crystalline and oriented filaments [27]. Two less perfect crystalline forms designated as band d-polymorphs with hexagonal packing of chains were detected at temperatures close to the melting point or after quenching [28], but no unit cell parameters or d-spacing values were reported. It is important to note, that according to refs.…”
Section: Crystalline Structure By X-ray Scatteringmentioning
confidence: 92%
See 1 more Smart Citation
“…All example deconvolutions in Figure 8 show that excellent fits with regression coefficients R 2 ≥ 0.99 were only possible if along with the two peaks of α−PA4 and the two amorphous halos AH 1 and AH 2 two more crystalline peaks were considered that should be assigned to an additional monoclinic phase designated by β-PA4. It was first described in the early work of Frederiks et al [43] and later on shown to co-exist with α-PA4 [24]. Table 6 shows that the values of the long spacings of these two PA4 phases almost coincide.…”
Section: Synchrotron Waxsmentioning
confidence: 64%
“…β-형 결정은 순수 한 조건에서는 찾아보기 힘들며, 주로 nylon 6의 β-구조와 유사하게 나타난다. δ-형 결정은 냉각 롤에서 배출된 nylon 4를 급속하게 냉각시킬 때 나타나며 이것은 무배향 조건에 서만 관찰된다 [9]. 일반적으로 필름을 연신하면 면배향이 생기기 때문에 X-선을 조사하는 방향에 따라 필름 표면에 수직인 방향(ND, through), 필름 표면에 평행하면서 연신 방향과 수직한 방 향(TD, edge), 필름 표면에 평행하면서 연신방향과 평행한 방향(OD, end)의 정보를 얻을 수 있다 [10].…”
Section: 서 론unclassified